Implementation of Government Regulation no. 94 of 2021 on Civil Servant Discipline from a Constitutional Perspective: A Case Study at the Sub-District Office of Na IX-X, North Labuhanbatu Regency - Siregar, Nurjannah; Suparmin, Sudirman (IHSA Institute, 2025)
This study aims to examine the implementation of Government Regulation No. 94 of 2021 concerning Civil Servant Discipline from the perspective of Siyasah Dusturiyah, using a case study at the Subdistrict Office of NA IX-X in Labuhanbatu Utara Regency. The research employs a normative-empirical method with a juridical-sociological approach through interviews and document analysis. The findings indicate that the enforcement of the regulation remains suboptimal due to the dominance of kinship-based organizational culture, limited legal comprehension among leaders, and the absence of an objective reward and punishment system. From the standpoint of Siyasah Dusturiyah, such leniency violates the principles of administrative justice and leadership accountability. Therefore, it is necessary to strengthen legal discipline training, implement a digital attendance system, and establish a structured mechanism of sanctions and incentives grounded in the values of maq??id al-shar?'ah, in order to build a disciplined, just, and recognized bureaucracy